Seismic Hazard Analysis for Earthquake Risk Mitigation and Sustainable Natural Resource and Environmental Management in Afghanistan - Rahimi, Mohammad Jawad; Kaiwaan, Abdulhai; Urfan, Khalid; Azimi, Sayed Javid; Namdar, Abdullah (Journal of Natural Sciences – Kabul University, 2026)
Afghanistan’s complex geological and tectonic setting makes the country highly susceptible to natural hazards, particularly earthquakes. This study focuses on seismic hazard analysis to evaluate earthquake risks in Afghanistan’s most vulnerable regions and to support effective risk mitigation strategies. The research aims to identify major seismic threats and assess their potential impacts on the sustainable management of natural resources and the environment. Given the significant damage earthquakes can cause across different regions, the study proposes strategic approaches to minimize their adverse environmental and resource-related consequences. Emphasis is placed on adopting holistic disaster risk management frameworks that consider Afghanistan’s socio-economic conditions and environmental constraints. Analytical models and hazard assessments demonstrate the critical role of government capacity-building and community-level training in disaster preparedness. The findings provide valuable guidance for policymakers and disaster managers, promoting informed decision-making through reliable seismic hazard data to enhance environmental sustainability and natural resource protection in earthquake-prone areas.